Obstacles and Solutions of MSMEs in Electronic Commerce during Covid-19 Pandemic: Evidence from Indonesia - Abu Muna Almaududi Ausat; Suherlan Suherlan (Universitas Muhammadiyah Jakarta, 2021)
The Covid-19 pandemic has forced business actors and/or MSMEs to adapt to the wave of disruption. There was a change in the way people shopped, a channel shift. People are abandoning traditional shopping in favor of shopping in the market online. However, there are barriers to MSMEs going digital, such as perceptions of benefits, business age, and HR competencies. This study aims to assist MSMEs in overcoming barriers to e-commerce use during the Covid-19 Pandemic. Because, Micro, Small, and Medium Enterprises are the most vulnerable businesses in a pandemic situation. This is a qualitative type of study. Data collection techniques include listening for and recording important information in order to conduct data analysis through data reduction, data display, and conclusion drawing. This study concludes that in the crisis era, MSMEs that have been in operation for a long time must determine a change in mindset and level of maturity in determining the stance or belief of each step of adopting new technology. Several education, training, exhibition, and mentoring programs must be implemented in order to meet the needs of qualified human resources in e-commerce.